Pengaruh Model Two Stay Two Stray (TSTS) Terhadap Kemampuan Menganalisis Unsur Instrinsik Cerita Di Kelas V SD Negeri 16 Pangkalpinang - Romina; Nurjanah; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2023)
The poor level of student analysis skills, notably in the Indonesian lesson, served as the driving force for this study. Additionally, since learning models are less diversified, students' analytical skills are still being developed. The goal of this research was to ascertain how the Two Stay Two Stray (TSTS) learning model affected fifth-grade students at SD Negeri 16 Pangkalpinang's capacity to analyse the intrinsic aspects. In this work, a non-equivalent control group design was employed in a quantitative investigation using a quasi-experimental design. The experimental group and the control group were not chosen at random in this design. 28 pupils from class VA and 28 students from class VB made up the study's subjects. Tests in the form of questions were administered in order to gather data. Students took the pretest and posttest in the form of an essay with five questions on it. The related sample t-test (polled variation) was utilised for hypothesis testing as well as the normality test, homogeneity test, and other data analysis procedures. The findings of this research suggest that the Two Stay Two Stray (TSTS) learning model has an impact on class V students at SD Negeri 16 Pangkalpinang's capacity to analyse the essential aspects of tales. The resultsof the hypothesis testing between the experimental class and the control class have tcount = 3.255 >ttable = 2.005, as can be observed from the data analysis findings. This demonstrates that Ha is welcomed. Thus, it can be said that the Two Stay Two Stray (TSTS) learning approach has an impact on students' capacity to evaluate the fundamental components of tales at SD Negeri 16 Pangkalpinang.